The Effect of Place Branding, Promotion and Tourism Product Attribute on Decision to Visit Through The Destination Image - Fuadillah, Nanda; Murwatiningsih, Murwatiningsih (Universitas Negeri Semarang, 2018)
The purpose of this study is to know the effect of place branding, promotion and attributes of tourism products to the decision to visit through the image of the destination. The population in this study is the visitors of Teluk Penyu beach tourism destination of Cilacap regency. The number of samples in this study were 150 respondents with Accidental sampling technique. Data analysis using Path Analysis with SPSS program version 21, where variables used include place branding (X1), promotion (X2), tourism product attribute (X3), destination image (Z1), Decision to visit (Y1). The result of the research found that all hypothesis of direct effect proposed is accepted where the significance value is <0,050, whereas for the intervening test obtained the total value of indirect effect> direct influence. This proves the hypothesis both directly and indirectly in this study are all accepted. Conclusion the better place branding, promotion and tourism product attributes can affect the image of the destination that will impact on the decision to visit.